2020
DOI: 10.1038/s41467-020-15689-9
|View full text |Cite
|
Sign up to set email alerts
|

Proper chromosome alignment depends on BRCA2 phosphorylation by PLK1

Abstract: The BRCA2 tumor suppressor protein is involved in the maintenance of genome integrity through its role in homologous recombination. In mitosis, BRCA2 is phosphorylated by Pololike kinase 1 (PLK1). Here we describe how this phosphorylation contributes to the control of mitosis. We identify a conserved phosphorylation site at T207 of BRCA2 that constitutes a bona fide docking site for PLK1 and is phosphorylated in mitotic cells. We show that BRCA2 bound to PLK1 forms a complex with the phosphatase PP2A and phosp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 47 publications
5
69
0
Order By: Relevance
“…Our characterization of BRCA2 phosphorylation by Plk1 (pH 7.8, T = 303 K), an important mitotic event, [35][36][37] permitted the quantification of two novel phosphosites, namely Thr219 and Thr226, which were modified with rates comparable to the previously reported Ser193 and Thr207 (Figure 5 a,c). [37,38] We also wanted to examine Oct4 phosphorylation by MAP kinase, which regulates Oct4 transcriptional activity. [31] In the presence of the MAP kinase p38a (pH 7.4, T = 298K), we noticed that Ser12, Ser111, and Thr118 in the classical MAP kinase target motif, Ser/Thr-Pro, were modified slower than Thr92 that is not located in a Ser/Thr-Pro motif ( Figure 5 b,d).…”
Section: Zuschriftensupporting
confidence: 68%
“…Our characterization of BRCA2 phosphorylation by Plk1 (pH 7.8, T = 303 K), an important mitotic event, [35][36][37] permitted the quantification of two novel phosphosites, namely Thr219 and Thr226, which were modified with rates comparable to the previously reported Ser193 and Thr207 (Figure 5 a,c). [37,38] We also wanted to examine Oct4 phosphorylation by MAP kinase, which regulates Oct4 transcriptional activity. [31] In the presence of the MAP kinase p38a (pH 7.4, T = 298K), we noticed that Ser12, Ser111, and Thr118 in the classical MAP kinase target motif, Ser/Thr-Pro, were modified slower than Thr92 that is not located in a Ser/Thr-Pro motif ( Figure 5 b,d).…”
Section: Zuschriftensupporting
confidence: 68%
“…Following the mapping of the interaction and the helicase stimulatory activity to the first 250 aa of BRCA2 (BRCA2 T1 ), we searched for BRCA2 missense variants identified in breast cancer patients that could disrupt the interaction with DDX5. We selected T207A, a breast cancer variant of unknown clinical significance (VUS) (clinvar/variation/VCV000052028.2) affecting a highly conserved residue in the region of BRCA2 T1 that we had characterized previously in the context of mitosis (Ehlén et al , 2020). Using DLD1 BRCA2‐deficient cells stably complemented with GFP‐tagged BRCA2 WT or BRCA2‐T207A, we performed a GFP‐trap pull‐down assay to detect bound DDX5.…”
Section: Resultsmentioning
confidence: 99%
“…BRCA2 tumor suppressor protein is involved in genome maintenance mechanisms including DNA repair by homologous recombination (HR) (Moynahan et al , 2001; Jensen et al , 2010), protection of stalled replication forks (RFs) (Schlacher et al , 2011), and faithful segregation of chromosomes (Daniels et al , 2004; Ehlén et al , 2020). Recent reports have revealed that BRCA2‐deficient cells accumulate DNA‐RNA hybrids or R‐loops (Bhatia et al , 2014; Tan et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, Plk1 has been proposed to work independently of Aurora B in this regard (Liu et al, 2012 ; Figure 3E ). Plk1 can affect kinetochore-microtubule stability in many different ways (Li et al, 2010 ; Bader et al, 2011 ; Hood et al, 2012 ; Maia et al, 2012 ; Kakeno et al, 2014 ; Shao et al, 2015 ), from a variety of different kinetochore subcomplexes (Nishino et al, 2006 ; Elowe et al, 2007 ; Amin et al, 2014 ; Kim et al, 2014 ; Dumitru et al, 2017 ; Ehlen et al, 2018 ). Therefore, these multiple different inputs from Plk1 may help to resolve the puzzling observations that Plk1 inhibition can either destabilize (Sumara et al, 2004 ; Lénárt et al, 2007 ) or stabilize (Foley et al, 2011 ) kinetochore-microtubule attachments under different conditions.…”
Section: Indirect Effects Of Microtubule Attachments On the Sacmentioning
confidence: 99%